CompTIA network+ N10-006 : complete video course - Wallace, Ken; Safari eBooks ([Place of publication not identified] : Pearson IT Certification, 2015., 2015)
"CompTIA Network+ N10-006 Complete Video Course is a comprehensive training course that brings CompTIA Network+ exam topics to life through the use of real-world demonstrations, animations, live instruction, and configurations, making learning these foundational networking topics easy and fun.Best-selling author, expert instructor, and double CCIE Kevin Wallace walks you through the full range of topics on the CompTIA Network+ N10-006 exam, including protocol reference models; network devices, topologies, and services; WAN technologies; network cables and connectors; network design; LAN technologies; network addressing and routing; unified communication; virtualization; network security; and network maintenance. This unique product contains multiple types of video presentations, including live instructor whiteboarding, real-world demonstrations, animations of network activity, dynamic KeyNote presentations, doodle videos, and hands-on router and switch CLI configuration and troubleshooting in real lab environments, enabling you to learn both the concepts and the hands-on application."--Resource description page.
Title taken from title screen (Safari, viewed July 8, 2015).
Presenter, Ken Wallace.
Keywords: Computing Technology Industry Association -- Examinations -- Study guides; Electronic books